Evaluation by metabolic profiling and in vitro autoradiography of two promising GnRH‐receptor ligands for brain SPECT imaging. (15th January 2020) - Fjellaksel, Richard; Moldes‐Anaya, Angel; Vasskog, Terje; Oteiza, Ana; Martin‐Armas, Montserrat; Hjelstuen, Ole Kristian; Hansen, Jørn H.; Riss, Patrick J.; Sundset, Rune
Abstract : The increased expression of gonadotropin releasing hormone receptor (GnRH‐R) in brain has been strongly linked to Alzheimer disease. Therefore, the development of radiolabeled imaging agents for GnRH‐R is relevant for early diagnosis of Alzheimer disease. We have recently disclosed the discovery of two promising compounds displaying nanomolar‐range affinity for the GnRH‐R. In the present study, a preclinical evaluation of the compound properties was performed to evaluate their potential as single photon emission computed tomography (SPECT) radiotracers for imaging the GnRH‐receptor. The compounds were assessed in vitro by performing serum stability analysis by human and rat serum, metabolic profiling by human liver microsomes, and exploratory rat brain autoradiography. The investigated compounds displayed satisfactory stability against human, rat serum, and liver microsomal metabolism, which favors their potential as SPECT‐imaging agents. Additionally, we identified and quantified the formation rate of the metabolites by fragmentation of up to five mass spectrometric stages. The GnRH‐R rat brain specificity of these compounds was tested in competition with a known ligand for the receptor and the in vitro autoradiography confirmed that compounds 3 and 4 binds to rat GnRH‐R in different rat brain regions. Abstract : Two promising GnRH‐receptor ligands based on a benzimidazole‐piperazine molecular scaffold displayed satisfactory stability against human‐, rat‐ serum and liver microsomal metabolism. Additionally, the GnRH‐R rat brain specificity of these compounds was tested in competition with a known ligand for the receptor and the in vitro autoradiography confirmed that compounds 3 and 4 binds to rat GnRH‐R in different rat brain regions which favors their potential as SPECT‐imaging agents.